Nexus Between Economic Efficiency, Healthcare, and Environmental Expenditures: A Perspective of BRI Countries - Hussain, Zahid; Miao, Cuifen; Zhao, Zhihao; Wang, Yingxuan (Frontiers in Public Health, 2022)
Public health and the environment are the most essential pillars, and play a vital role in the economy. In order to better public health, the economic and environmental atmosphere must be stable and clean, respectively. Thus, this paper emphasizes on nexus between economic, public health, and the environment. Therefore, the objective of this paper is whether healthcare and environmental expenditures affect economic efficiency and vice versa. So, this study evaluates the performance of the country's economic efficiency and investigates the effect of healthcare and environmental expenditures for 62 Belt and Road Initiative countries for the period from 1996 to 2020. Suitable input-output variables are employed under the framework of DEA-window and Malmquist Index Productivity, and Stochastic Frontier Analysis (SFA). In addition, this study estimates the relationship between economic efficiency, healthcare, and environmental expenditures by fixed and random effects models. Therefore, the analytical outcomes reveal that countries are economically efficient. On the contrary, SFA estimation concludes that countries are found to be inefficient, because higher variation is exists in efficiency change compared to technological efficiency change and total factor productivity change on average. In addition, it is worth notable that healthcare and environmental expenditures improve the country's economic efficiency. Furthermore, public health is also influenced by economic efficiency. Thus, this study suggests that countries should better utilize given resources and invest a specific portion of national income in order to improve economic efficiency.